Biological treatments for co-occurring eating disorders and psychological trauma: a systematic review - van Beers, Ella; de Vries, Irene; Planting, Caroline; Christ, Carolien; de Beurs, Edwin; van den Berg, Elske (Frontiers in Psychiatry, 2025)
IntroductionMany people with eating disorders report having experienced childhood maltreatment or a traumatic event prior to developing an eating disorder. Although many people with eating disorders have significant traumatic exposure or symptoms of post-traumatic stress disorder, very little research has examined the effects of combined treatments for this group. The purpose of this systematic review was to synthesize all existing research on biological treatments for those with eating disorders and psychological trauma, evaluate their safety, and identify future areas of research in this area to support patients with eating disorders and psychological trauma.MethodA multi-step literature search, according to an a priori protocol was performed on PubMed, Embase, APA PsycINFO, Web of Science, Scopus and Cochrane Central. Studies needed to include a biological intervention and report on at least one eating disorder or psychological trauma outcome. Given the limited research in this area, minimal exclusion criteria were applied. A quality assessment of all included studies was completed using the Risk of Bias in Non-Randomized Studies-or Interventions (ROBINS-I) tool.ResultsAfter removing duplicates, 2623 article titles and abstracts were screened, with 43 articles selected for a full-text review. Following the full-text review, 11 articles met the inclusion criteria. The biological treatments examined included repurposed medications (n = 3), ketamine (n = 2), repetitive transcranial magnetic stimulation (rTMS; n = 2), deep brain stimulation (n =1) electroconvulsive therapy (ECT; n = 1), 3,4-methylenedioxymethamphetamine (MDMA; n = 1), and neurofeedback (n = 1). All studies reported on some improvement in either eating disorder or trauma pathology, with the strongest effect for repetitive transcranial magnetic stimulation and MDMA. While some effects were promising, missing data and selective reporting limited the interpretability of the findings. Adverse events across interventions were common.ConclusionAlthough psychological trauma is common in those with eating disorders, very few treatments have been evaluated in this population. Future work should aim to investigate biological treatments for those with co-occurring eating disorders and psychological trauma, as these evolving treatments show potential benefits for this complex group.